Synthesis of quinazolinones derivatives an antiproliferative agent against human lung carcinoma cells - Deshmukh, Satish Uttamrao; Kharat, Kiran Ramesh; Kadam, Gajanan Gulabrao; Pawar, Rajendra Pundlikrao (European Journal of Chemistry, 2017)
2,3‐Dihydroquinazolin‐4(1H)‐one derivatives (3a-p) were synthesized in excellent yields. These compounds were screened for antiproliferative activity against A549 cells and were found as potent cytotoxicity. Compounds A4, A8, A10 found to be more promising antiproliferative against the lung carcinoma A549 cells. IC50 values for compounds A4, A8 and A10 were found to be 8.6, 8.9 and 8.1 μg/L against A549 cells, respectively.